Inflation and Accumulation. The Case of Israel - Jonathan Nitzan; Shimshon Bichler (Science & Society, 2000)
The paper offers a new theoretical framework for linking inflation and accumulation, with the Israeli experience as a case study. The focal point is the process of differential accumulation by the largest core firms. The theory of differential accumulation suggests that the relative power of these firms can be augmented either through `breadth' (relative employment) or `depth' (relative profit per employee). In the Israeli case, inflation accelerated since the 1970s when the large core firm began shifting their emphasis from breadth to depth. The paper examines the political economic conditions typical to each of these regimes, why these conditions changed in Israel, and how the distributive gains of the core firms pushed the country onto the brink of hyperinflation. It then articulates the inherent limits of a `depth' regime, why Israel reached those limits during the early 1980s, and how this brought the inflation spiral to an end.
Keywords: 330; arms; breadth; capital; capitalism; corporation; crisis; DA; depth; distribution; finance; globalization; inflation; institutionalism; Israel; M&A; merger; Middle East; military; money; power; prices; profit; stagflation; state; TNC